2020
DOI: 10.1017/s000712341900067x
|View full text |Cite
|
Sign up to set email alerts
|

The British Academy Brian Barry Prize Essay: Representing the Future: The Interests of Future Persons in Representative Democracy

Abstract: As a reaction against contemporary democracy's inherent short-sightedness in solving problems that are likely to affect distant future generations, there has been a recent increase in proposals for different kinds of democratic representation of future persons. This article shows that even though there can be no such thing as political representation of future persons, the relevant affected interests of the as-yet unborn can still be taken into consideration in political decision making. This aim is achieved b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…The survey has shown that the respondents generally approve of including the needs of future generations in the site selection, but the actual implementation is contested. Following the findings of Campos (2021), first positive developments regarding intergenerational justice are observable in Germany, especially by the foundation of the Council of the Young Generation. Such an institution can help bridge the gap between current and future generations but requires constant participation and interest from young(er) participants.…”
Section: Discussionmentioning
confidence: 94%
“…The survey has shown that the respondents generally approve of including the needs of future generations in the site selection, but the actual implementation is contested. Following the findings of Campos (2021), first positive developments regarding intergenerational justice are observable in Germany, especially by the foundation of the Council of the Young Generation. Such an institution can help bridge the gap between current and future generations but requires constant participation and interest from young(er) participants.…”
Section: Discussionmentioning
confidence: 94%
“…The council members argue that young people will actually experience the implementation of the repository and are therefore affected more strongly. Such institutions can help to build a bridge to the next generations if carried out constantly throughout the process (Campos 2021). This development provides an example of how procedural justice in the current process contributes to intergenerational justice in the future.…”
Section: Methodsmentioning
confidence: 96%
“…Tremmel (2021) argues in favor of 'institutions for future generations.' This can be enabled by improving the political representation of children as links to future generations (Campos 2021). This representation needs to be understood as a representation of claim rights (Campos 2019).…”
Section: On the Importance Of Intergenerational Justicementioning
confidence: 99%
“…Since future generations, by definition, do not yet exist and thus cannot authorize or engage with their potential representatives, there is no consensus in the literature as to whether and how they can be represented at all, and, by extension, whether institutional innovations such as the ombudsman in Hungary or the commissioner in Wales should be normatively motivated, framed, conceptualized, and analyzed in terms of political representation (Beckman, 2023;Campos, 2021;Ekeli, 2005;Gonzalez-Ricoy & Rey, 2019;Heyward, 2008;Jensen, 2015;Jones et al, 2018;Karnein, 2016;Kinski & Whiteside, 2023;Rose, 2019;Smith, 2020;Thompson, 2010;Warren, 2023;Zwarthoed, 2018).…”
Section: Introductionmentioning
confidence: 99%